2015
DOI: 10.1007/s11244-015-0400-2
|View full text |Cite
|
Sign up to set email alerts
|

Proline-Derived Structural Phases on Cu{311}

Abstract: Structural phases formed by adsorption of L-proline onto a Cu{311} surface in ultra-high vacuum were investigated using reflection-absorption infrared spectroscopy, low-energy electron diffraction and scanning tunnelling microscopy. An ordered structural phase formed by selfassembly of L-prolinate with (2,1;1,2) periodicity, and a transition from pure l3 bonding to a mixture of l3 and l2 bonding with increasing exposure at 300 K, were observed. This behaviour has broad parallels with that previously seen with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Alternatively, adsorbed chiral molecules may bestow chirality on metal surfaces. With relatively inert metals such as copper, it has been shown that the adsorption of chiral molecules can lead to the formation of many ordered homochiral structures. Perhaps more interestingly, on the surface of more active metals such as Pt or Pd, chiral sites can be generated via the adsorption of submonolayer coverages of “templating” chiral molecules. In that case, it is presumed that the adsorbates form supramolecular structures on the surface containing chiral pockets that can act as enantioselective adsorption sites for other adsorbates. Unfortunately, as mentioned before, these ideas generated from experiments using model systems are yet to translate into the design of realistic enantioselective catalysts.…”
Section: Selectivitymentioning
confidence: 99%
“…Alternatively, adsorbed chiral molecules may bestow chirality on metal surfaces. With relatively inert metals such as copper, it has been shown that the adsorption of chiral molecules can lead to the formation of many ordered homochiral structures. Perhaps more interestingly, on the surface of more active metals such as Pt or Pd, chiral sites can be generated via the adsorption of submonolayer coverages of “templating” chiral molecules. In that case, it is presumed that the adsorbates form supramolecular structures on the surface containing chiral pockets that can act as enantioselective adsorption sites for other adsorbates. Unfortunately, as mentioned before, these ideas generated from experiments using model systems are yet to translate into the design of realistic enantioselective catalysts.…”
Section: Selectivitymentioning
confidence: 99%
“…After adsorption and subsequent annealing to 350 -420 K, the pyrrolidine ring dehydrogenates and hydrogen is evolved, as indicated by reflection absorption infrared spectroscopy (RAIRS) and confirmed by TPRS. 38 At temperatures of 460 -480 K, the carboxylate group dissociates from the dehydrogenated ring and desorbs from the surface as CO2 with the dehydrogenated ring desorbing as pyrolle at slightly higher temperatures.…”
Section: Figurementioning
confidence: 99%
“…These m/z ratios were selected based on TPRS performed by other research groups. 36,38,40,50,51 Figure 3 shows the TPRS signals versus temperature for the m/z ratios monitored during D-Pro decomposition. The peak at 475 K in the m/z = 2 signal is consistent with hydrogen desorption due to the dehydrogenation of the pyrrolidine ring.…”
Section: Pro Decomposition Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The UHV system used in this work has been fully described in our previous work, [35][36][37] so here we describe the relevant sections only briefly. The system is divided into three different levels, each accommodating different components.…”
Section: Rairs Experimentsmentioning
confidence: 99%